Concrete Compressive Strength of Post Combustion With and Without Watering - Rafki Imani; Rita Nasmirayanti; Julio Rendi Akbar (Applied Research on Civil Engineering and Environment (ARCEE), 2023)
The strength of the building structure after a fire is determined by the length of time the fire takes place and the cooling process used. According to several previous studies, it is said that the longer the concrete burns, the lower the quality of the concrete will be. This study aims to observe the compressive strength of concrete after the combustion process by cooling through experimental trials on 21 samples of cube model concrete. The concrete sample consisted of three samples of normal concrete and 18 samples of concrete that would be given combustion treatment and the quality of the design concrete was K250. Three samples of normal concrete were tested at the age of 14 days, then 18 samples were prepared for the combustion process with normal fire. A total of nine samples of concrete were treated with combustion for one hour, two hours and three hours with normal cooling in the open air as many as three samples each. Meanwhile, nine other concrete samples that had undergone combustion were given cooling treatment by sprinkling with water. The average compressive strength of concrete with a duration of one hour, two hours and three hours without water cooling respectively is 320.05 kg/cm2, 285.65 kg/cm2 and 235.21 kg/cm2, with the percentage of decrease in the quality of concrete to normal concrete respectively is 9%, 19%, and 33%. Meanwhile, the average compressive strength of concrete with water cooling for the same duration of combustion is 295.72 kg/cm2, 245.34 kg/cm2 and 210.17 kg/cm2, with the percentage of decrease in the quality of concrete to normal concrete respectively is 16%, 30%, and 40%. Based on the results of this study, the duration of combustion and the cooling treatment used can reduce the quality of concrete compared to normal concrete.